Characterisation of the lipid profile of the portuguese population - Mariano, Cibelle (2016)
Cardiovascular disease (CVD), particularly coronary heart disease (CHD) and stroke, are the leading cause of morbidity and mortality worldwide. The common forms of CVD have a complex aetiology in which interactions between multiple genetic and environmental factors play an important role.